2012
DOI: 10.4490/algae.2012.27.4.259
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and molecular study of Pterosiphonia arenosa sp. nov. (Rhodomelaceae, Rhodophyta) from Jeju Island, Korea

Abstract: The genus Pterosiphonia is composed of 22 species worldwide and four of these species have been reported in the North-East Asia. In Korea, P. pennata originally described from the Mediterranean Sea has been previously recorded from the southern coast as a widespread species. In order to confirm the same species from Korea and Mediterranean, we observed the morphology of Korean Pterosiphonia specimen and analyzed rbcL sequences for inferring phylogenetic relationships among similar congeners. Korean entity was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…A pit like morphology was seen and developed with a flow rate in view of the number of pits. It was shown that a pit like morphology is caused by the inclusion dissolution at the early stage, and is developed into a scallop (orange peel) pattern [10]. From this, it is presumed that the density and size of a pit like morphology is an index of the FAC rate.…”
Section: Resultsmentioning
confidence: 99%
“…A pit like morphology was seen and developed with a flow rate in view of the number of pits. It was shown that a pit like morphology is caused by the inclusion dissolution at the early stage, and is developed into a scallop (orange peel) pattern [10]. From this, it is presumed that the density and size of a pit like morphology is an index of the FAC rate.…”
Section: Resultsmentioning
confidence: 99%
“…We used the same program with the same setting and 1000 replications to generate bootstrap values for these phylogenies. Bayesian and Kang 2011) and rbcLF145-rbcLR898 and rbcLF762-rbcLR1442 (Kim et al 2012). For samples that failed amplification, we redesigned the primers (e.g., CrbcLF725…”
Section: Methodsmentioning
confidence: 99%
“…Molecular taxonomy is especially useful for species that are wide-ranging and have few clear-cut morphological diagnostic criteria (Kim et al 2012a, Yang et al 2013. We assembled a collection of specimens of (i) C. lactuca from the subtidal zone of Jeju Island, Korea, (ii) C. luxurians from intertidal zone of Chiba, Japan, and (iii) C. seminervis from the type locality in Spain.…”
Section: Methodsmentioning
confidence: 99%